Analisis faktor-faktor produksi usaha budidaya gracilaria verrucosa menggunakan metode tebar di tambak Desa Lakawali Pantai Kecamatan Malili Kabupaten Luwu Timur Provinsi Sulawesi Selatan - Suwanti, Anggi; Yusuf, Sarini; Ruslaini (Jurnal Sosial Ekonomi Perikanan, 2021)
Production factors such as capital, labor and land area as well as business experience has been identified to affect the industry’s production output, including seaweed cultivation using long line method in coastal areas. However, it is currently unknown whether such production factors affect seaweed culture in brackish pond using spread method or not. The purpose of this study is to determine whether the factors of capital, labor, land area and business experience affect the production of agar producing seaweed (Gracillariaverrucosa) farmed in brackish ponds using spread method.This research was conducted from February to March 2020 in Lakawali Beachi Village, Malili, East Luwu, South Sulawesi. Cluster random sampling method was applied to select 10 farmers from a population of 30 farmers in the study site. Data were collected through direct interviews using structured questionnaires. The data observed were the respondent's identity, age, education level, family dependents, and production inputs used in seaweed cultivation (capital, labor, land area, and business experience). Data were analyzed using multiple non-linear regression in SPSS 16.0 program. The results showed that the factors that had a significant and positive effect on seaweed production in the study site were land area and business experience with a regression coefficient value of 0.871. Whereas other factors such as capital and labor did not have a significant effect withregression coefficient value of 0.023 and -0.014, respectively. Therefore, the development of agar producing seaweed aquacultureshould take land area and business experience into consideration, whereas capital and labor can be ignored.